The discriminative ability of peripheral and axial bone measurements to identify proximal femoral, vertebral, distal forearm and proximal humeral fractures: a case control study - Clowes, Jackie A.; Eastell, Richard; Peel, Nicola F. A. (Osteoporosis international, 2005)
Previous studies evaluating peripheral bone measurement devices have often used discontinued technologies, compared single devices, only evaluated a single fracture syndrome or failed to make a comparison with central densitometry, which is currently the gold standard for fracture discrimination. We have used a case control study to evaluate the ability of different peripheral and central bone techniques to discriminate between fracture cases and controls, determine the impact of different measurement sites, evaluate the role of measuring the cortical or trabecular envelopes using quantitative computed tomography (QCT) and determine the impact of using combinations of sites and techniques on fracture discrimination. We recruited postmenopausal women with proximal femoral (n=53), vertebral (n=73), distal forearm (n=78) or proximal humeral (n=75) fractures, and 500 population-based women (age 55-80 years). All subjects had measurements of the spine, total hip and distal forearm with dual-energy X-ray absorptiometry (DXA), distal forearm QCT and quantitative ultrasound (QUS) of the heel (four devices), finger (two devices), radius and metatarsal. The association of each device with fracture was expressed as the age-adjusted standardized odds ratios (sOR) per 1-SD decrease of population variance. The association of bone measurements with fracture was site-specific. We found the hip (sOR up to 3.40) and vertebral (sOR up to 4.67) fractures were more closely associated with central bone measurements than upper limb fractures (sOR 1.96 and 2.05). The performance of heel broadband ultrasound attenuation (sOR 2.09-2.41), heel speed of sound (sOR 1.79-2.28) and peripheral BMD (sOR 2.07 and 2.24) was comparable with total hip (sOR 2.46) and lumbar spine DXA (sOR 2.31) in discriminating all types of osteoporotic fracture. In general, measuring cortical or trabecular envelopes did not increase sOR. However, combining different measurement sites or technologies provided additional information, which was independent of total hip BMD. The ability of different bone measurements to discriminate between fracture cases and controls is device- and site-specific, with additional information obtained by combining measurement sites and technologies.